Searching reconciliation: Spanish diplomacy to the Dominican Republic after the failure of the re-annexation, 1865-1879 (Tzintzun, Revista de Estudios Históricos, 2016)
The failure of the re-annexation of the Dominican Republic to Spain between1861 and 1865 conditioned the relations between both countries over the nextdecade. Spanish-Dominican relations were not only mediated by the increasedrisk of annexation of the Caribbean republic to the United States, especially duringthe administrations of Cabral and Baez, but also by the outbreak of the Cubancrisis in 1868. This complex scenario forced the Spanish diplomacy to attempt arapprochement with its former colony. The normalization of relations between thetwo countries would be, however, hampered by internal Dominican instability andbecause of the sympathy the Cuban insurgents found among important sectorsof society and the Dominican political class. This paper analyzes this process andexplores the reasons that postponed the resumption of diplomatic relations betweenDominicans and Spaniards until the late 1870’s.
Keywords: re-annexation; diplomacy Spanish-Dominican; Cuban crisis; Dominican political class